2006
DOI: 10.1038/sj.ijo.0803483
|View full text |Cite
|
Sign up to set email alerts
|

Changes in fat-free mass during significant weight loss: a systematic review

Abstract: Objective: To identify the proportion of weight lost as fat-free mass (FFM) by various weight loss interventions. Methods: Medline and Embase were systematically searched for reliable measurements of FFM before and after weight loss of 410 kg and eligible data were pooled. In a fixed effect model of % FFM loss/weight loss (%FFML), linear regression analysis was used to determine the influence of degree of caloric restriction, exercise, magnitude of weight loss, initial body mass index (BMI) and type of surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
316
3
12

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 377 publications
(355 citation statements)
references
References 59 publications
(43 reference statements)
24
316
3
12
Order By: Relevance
“…Adding exercise to the low‐calorie diet regimen, however, changes this ratio by increasing FM losses and reducing FFM losses after just 4 weeks of intervention (Chaston et al. 2007; Heymsfield et al. 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding exercise to the low‐calorie diet regimen, however, changes this ratio by increasing FM losses and reducing FFM losses after just 4 weeks of intervention (Chaston et al. 2007; Heymsfield et al. 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Chaston et al. (2007) reported that exercise in addition to calorie restriction achieved ~22% of fat‐free mass loss. The type and intensity of physical activity included will further impact the ΔFFM/ΔWeight ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Somewhat lower losses in FFM (expressed in per cent of weight lost) have been observed with diets providing more than 3 347 kJ (800 kcal) per day (14.0 % (IQR: 4-24 %)) than with diets providing fewer than that (23.4 % (IQR: 15.4-31.4 %)) (Chaston et al, 2007).…”
Section: Energymentioning
confidence: 99%
“…However, the level at which losses of FFM should be considered to be adverse is unclear. A systematic review and meta-analysis of human intervention and observational studies (Chaston et al, 2007), which assessed changes in fat mass and FFM by dualenergy X-ray absorptiometry (DEXA), or underwater weighing after weight loss of more than 10 kg, showed a median loss of FFM of 23.4 % of the body weight loss (interquartile range (IQR): 15.4-31.4 %) with VLCDs (three studies (136 subjects)), of 22.5 % (11.5-33.5 %) with VLCDs plus exercise (two studies (40 subjects)) and 14.0 % (IQR: 4-24 %) with LCDs (eight studies (241 subjects)) with study periods between 6 and 52 weeks. In regression analyses, losses in FFM were explained by the energy content of the diet only.…”
Section: Metabolic Consequences Of Weight Lossmentioning
confidence: 99%
“…It is well known that body fat is associated with significant amounts of non-fat tissue involved in its mechanical and physiological support so that changes in FM are generally accompanied by changes in FFM leading to a correlation between them (e.g. Brožek, 1963;Burton, 2010Burton, , 2012. Chaston et al, 2007;Dixon et al, 2007;Forbes, 1987;Heymsfield et al, 2011Heymsfield et al, , 2014Keys and Brožek, 1953;Webster et al, 1984).…”
Section: Introductionmentioning
confidence: 99%